Growth Performance of Sensi Native Chickens Under an Intensive Rearing System - Junaedi, Junaedi; Khaeruddin, Khaeruddin; Amin, Muhammad (Tarjih Tropical Livestock Journal, 2025)
This study aims to analyze the growth pattern of body weight of superior Sensi native chickens in an intensive maintenance system and to evaluate the effectiveness of the system in supporting production performance. This study was conducted for 75 days, covering three maintenance phases: starter (1–21 days), grower (22–42 days), and finisher (43–75 days), with a sample of 20 chickens from a population of 275 DOCs observed individually. The method used was a field experiment in a closed cage with ad libitum feeding. Data collected included initial body weight, weekly weight, daily weight gain (DWG), feed conversion (FCR), and mortality. The results showed a sigmoid growth pattern, where body weight increased consistently from 28.25 g in DOC to 1080 g on the 75th day. The highest DWG was recorded at 75 days of age at 14.02 g/head/day. The FCR value of 2.31 indicates good feed efficiency for native chickens, with a very low mortality rate of 0.88%. The conclusion of this study is that Sensi native chickens have high potential to be cultivated in an intensive system, both in terms of growth, feed efficiency, and resistance to mortality. These results can be a reference for breeders, researchers, and policy makers in developing superior native chicken cultivation strategies based on scientific data and production efficiency.